2004
DOI: 10.1111/j.1463-5224.2004.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different dose schedules of travoprost on intraocular pressure and pupil size in the glaucomatous Beagle

Abstract: Travoprost instilled once daily (a.m. or p.m.) as well as twice daily produces significant decreases in IOP and PS in the glaucomatous Beagle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…In persistent or advanced cases of glaucoma, twice-daily application is preferred and has been shown experimentally to dampen daily IOP fluctuations better than once-daily application. 59,61,62 Latanoprost may be indicated after phacoemulsification to mitigate POH, but a recent study found no significant beneficial effect with regard to the frequency or severity of POH when applying this medication topically at the end of surgery. 11…”
Section: Clinical Usementioning
confidence: 97%
See 1 more Smart Citation
“…In persistent or advanced cases of glaucoma, twice-daily application is preferred and has been shown experimentally to dampen daily IOP fluctuations better than once-daily application. 59,61,62 Latanoprost may be indicated after phacoemulsification to mitigate POH, but a recent study found no significant beneficial effect with regard to the frequency or severity of POH when applying this medication topically at the end of surgery. 11…”
Section: Clinical Usementioning
confidence: 97%
“…These drugs possess the same mechanism of action as latanoprost, bind to the same FP receptors, and have been shown to have similar efficacy to latanoprost in both normotensive and glaucomatous dogs. [59][60][61][62][63] The most significant difference between these drugs and latanoprost is the cost because generic formulations are not currently available for these medications. Use of these drugs is usually cost prohibitive in many cases.…”
Section: Other Prostaglandin Analoguesmentioning
confidence: 99%
“…Past prostaglandin studies in both normal and glaucomatous dogs indicate that the ocular hypertensive dogs appear more sensitive and demonstrate greater declines in IOP than normotensive dogs (20)(21)(22)(23)(24)(25). Latanoprost, using normal dogs, produced a mean decline in IOP of 3 mmHg, or approximately 25% (25), but with glaucomatous dogs the average decline in IOP was approximately 50% for one day of drug administration, and 50%-78% after 4 days of twice-daily latanoprost, brimatoprost, and travoprost administrations (20,22).…”
Section: Discussionmentioning
confidence: 99%
“…All of these prostaglandins caused significant reductions in IOP and, often, miosis (20)(21)(22). In early studies in normotensive and glaucomatous Beagles, two drugs similar to latanoprost (PGF 2␣ -17-diphenyl and PGF 2␣ -isopropyl ester) lowered IOP, with the greatest decline occurring in the glaucomatous dogs (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation